The Impact of Teacher Feedback towards Students’ Learning Outcomes - Mutmainnah Muinuddin M Dyah; Rafi’ah Nur; Salasiah Ammade; Ammang Latifa; Siti Hajar Larekang (Universitas Muhammadiyah Enrekang, 2024)
Teacher feedback has always been understood as knowledge regarding the strengths and weaknesses of students' academic performance as well as suggestions for improvement. This research aims to find out students’ perceptions about teacher feedback and how teacher feedback influences the learning outcomes of English Education Study Program Students at Muhammadiyah University of Enrekang. The subjects of this research were 10 third semester students. The data analysis technique uses SPSS V.25 by looking for the influence of teacher feedback on student learning outcomes. Teacher feedback is measured using a questionnaire and student learning outcomes are obtained from writing tests. The research results show that teacher feedback and student learning outcomes is in the medium category. Based on the results of analysis and hypothesis testing, the significant value is 0.013 < 0.05. It showed that H0 is rejected and H1 is accepted. Hence, it can be concluded that there is a significant influence between teacher feedback on the students’ learning outcomes of English education study program students at Muhammadiyah University of Enrekang.